Implementation of Holistic Learning Based on Islamic Habituation and Montessori - Yulia Dewi Rantamsari; I. Ismail (Golden Ratio of Data in Summary, 2026)
This study aims to describe the implementation of holistic learning based on Islamic habituation and the Montessori method at TPA Az-Zahra. A holistic approach in early childhood education emphasizes the integrated development of all aspects of children’s growth, including spiritual, moral, cognitive, socio-emotional, language, and motor skills. Islamic habituation is applied through routine activities such as daily prayers, simple worship practices, daily manners, and the internalization of noble moral values. Meanwhile, the Montessori approach is implemented through a structured learning environment, the use of sensorial learning materials, freedom for children to choose activities, and child-centered learning. This research uses a qualitative approach with a case study method. Data were collected through observation, interviews with teachers and the school principal, and documentation of learning activities. The results show that the integration of Islamic habituation and the Montessori method creates a conducive learning environment that fosters independence, discipline, and religious character in children while encouraging meaningful participation in learning activities appropriate to their developmental stages.